Diboraanthracene‐Doped Polymer Systems for Colour‐Tuneable Room‐Temperature Organic Afterglow. Issue 4 (14th December 2022) - Jovaišaitė, Justina; Kirschner, Sven; Raišys, Steponas; Kreiza, Gediminas; Baronas, Paulius; Juršėnas, Saulius; Wagner, Matthias
Abstract: Organic ultralong room temperature phosphorescence (RTP), or organic afterglow, is a unique phenomenon, gaining widespread attention due to its far‐reaching application potential and fundamental interest. Here, two laterally expanded 9, 10‐dimesityl‐dihydro‐9, 10‐diboraanthracene (DBA) derivatives are demonstrated as excellent afterglow materials for red and blue‐green light emission, which is traced back to persistent thermally activated delayed fluorescence and RTP. The lateral substitution of polycyclic DBA scaffold, together with weak transversal electron‐donating mesityl groups, ensures the optimal molecular properties for (reverse) intersystem crossing and long‐lived triplet states in a rigid poly(methyl methacrylate) matrix. The achieved afterglow emission quantum yields of up to 3 % and 15 %, afterglow lifetimes up to 0.8 s and 3.2 s and afterglow durations up to 5 s and 25 s (for red and blue‐green emitters, respectively) are attributed to the properties of single molecules. Abstract : Two diboraanthracene compounds are presented as a new class of room temperature organic afterglow materials for colour‐tuneable polymer‐based systems. The afterglow consists of persistent thermally activated delayed fluorescence and organic ultralong room temperature phosphorescence.